Estimation of displacement efficiency for Devonian formations based on the results of specialized well tests - I. M. Indrupskiy; K. V. Kovalenko; D. M. Gazizova; A. F. Sibgatullin; D. P. Anikeev; N. V. Shabalin; K. R. Sadeev; A. A. Lutfullin (Georesursy, 2024)
The displacement efficiency and residual oil saturation are the most important characteristics determining the recoverable volumes of oil and the waterflooding efficiency. The main data about these parameters are provided by laboratory core studies. Specialized field tests make it possible to evaluate the same characteristics in-situ, directly on a well, thus excluding the influence of scale effect and impact of core sampling and preparation.This paper presents the results of a field study to evaluate the displacement efficiency and residual oil saturation on a well draining terrigenous Devonian formations on one of the areas of the Romashkinskoye field. The results are compared with generalized dependencies based on core data. Significant influence of the scale effect (the effect of sweep multiplicity) on the estimated parameter values was noted, which indicates the need to supplement laboratory experiments with specialized field studies.